Use of glatiramer acetate between 2010–2015: effectiveness, safety and reasons to start GA as first or second line treatment in Swiss multiple sclerosis patients - Zecca, Chiara; Disanto, Giulio; Sacco, Rosaria; Riccitelli, Gianna C.; Gobbi, Claudio (BMC neurology, 2019)
Background Glatiramer acetate (GA) is one of the first therapies approved for multiple sclerosis (MS). We prospectively included and monitored drug-naïve and pre-treated MS patients who had been prescribed GA for 1 year, to investigate reasons for GA prescription, its effectiveness and safety in real life clinical practice. Methods One year, prospective, multicentre, observational study performed between 2010 and 2015 in consecutive MS and clinically isolated syndrome patients starting GA as a first (“naïve”) or second (“switcher”) line therapy. Primary endpoint was the annualized relapse rate (ARR) over 1 year of GA treatment (from baseline, V1, to 12 months, V2) in naïve and switchers compared to previous 24 months. Secondary endpoints were: EDSS changes between V1 and V2, frequency of adverse events, and reasons for prescribing and discontinuing GA. Baseline demographics and clinical characteristics were retrieved from medical records, and outcome measures were documented at V1 and V2, and in case of clinical worsening. Results One hundred ninety-four consecutive patients were monitored over 12 months ( N = 64 naïve, N = 130 switchers). Side effect profile (naïve = 36%, switchers = 28%) and comorbidities (naïve = 31%, switchers = 15%) were the most frequent reasons to start GA. The ARR was reduced in both naïve and switchers during V1–2 as compared to the 24 months preceding V1 [naïve: 0.0 (0.0–0.0) vs 0.5 (0.5–1.0, p = 2.9e-10); switchers: 0.0 (0.0–0.0) vs 0.5 (0.0–0.5, p = 0.022)]. EDSS at V2 was significantly reduced only in naïve [(1.5 (1.0–2.5) vs 2.0 (1.5–2.5), p = 0.003)]. Naïve status and EDSS at V1 were negatively associated with EDSS change between V1-V2 in multivariable analysis (regression coefficient = − 0.436, p = 0.008, and regression coefficient = − 0.263, p = 6.18e-05, respectively). No new unexpected AE was reported. Conclusion In our Swiss cohort, GA was prescribed mainly to naïve or switcher MS patients fearing interferon related side effects, with various comorbidities or considering pregnancy, and showed effectiveness and safety comparable with data of previous GA studies.